Association of Agricultural, Occupational, and Military Inhalants With Autoantibodies and Disease Features in US Veterans With Rheumatoid Arthritis. Issue 3 (29th January 2021) - Ebel, Ariadne V.; Lutt, Gabrielle; Poole, Jill A.; Thiele, Geoffrey M.; Baker, Joshua F.; Cannon, Grant W.; Gaffo, Angelo; Kerr, Gail S.; Reimold, Andreas; Schwab, Pascale; Singh, Namrata; Richards, J. Steuart; et al.
Abstract : Objective: To determine the association of inhalant exposures with rheumatoid arthritis (RA)–related autoantibodies and severity in US veterans. Methods: Participants in the Veterans Affairs Rheumatoid Arthritis (VARA) registry were mailed surveys assessing occupational, agricultural, and military inhalant exposures. Demographic characteristics, disease activity, functional status, and extraarticular features were obtained from the VARA registry, while HLA–DRB1 shared epitope (SE) status, anti–cyclic citrullinated peptide (anti‐CCP) antibodies, and rheumatoid factor (RF) were measured using banked DNA/serum from enrollment. Associations between inhalant exposures and RA‐related factors (autoantibodies, severity, and extraarticular features) were assessed using multivariable linear and logistic regression models adjusted for age, sex, race, and tobacco use and stratified by SE status. Adjusted odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated. Results: Questionnaires were returned by 797 of 1, 566 participants (50.9%). Survey respondents were older, more often White or male, and less frequently smokers, and had lower disease activity compared to nonrespondents. Anti‐CCP positivity was more common among veterans exposed to burn pits (OR 1.66 [95% CI 1.02, 2.69]) and military waste disposal (OR 1.74 [95% CI 1.04, 2.93]) independent of other factors. Among participants who were positive for SE alleles, burn pit exposure (OR 5.69 [95% CI 2.73, 11.87]) and military waste disposal exposure (OR 5.05 [95% CI 2.42, 10.54]) were numerically more strongly associated with anti‐CCP positivity. Several inhalant exposures were associated with the presence of chronic lung disease, but not with the presence of RF or the level of disease activity. Conclusion: Military burn pit exposure and military waste disposal exposure were independently associated with the presence of anti‐CCP antibodies in RA patients. These findings are consistent with emerging evidence that various inhalant exposures influence autoantibody expression and RA risk.